Pengaruh Kepemimpinan, Motivasi Kerja dan Komunikasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja - Estiningsih Estiningsih (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This study includes explanatory namely a study model to find and explain causal relationships between variables through testing hypotheses that use a quantitative approach with qualitative analysis which intends to explain the causality relationship between variables through hypothesis testing and analysis of the research variables. By testing the influence between variables related to Leadership, Communication, Employee Performance and Job Satisfaction.The results of the study that the effect of variable job satisfaction (Y1) is influenced by leadership (X1), motivation (X2) and communication (X3) together by 42.9% while the remaining 57.1% is influenced by other variables outside this research model. While the effect of variable employee performance (Y2) is influenced by leadership (X1), motivation (X2), communication (X3) and work satisfaction (Y1) together by 45% while the remaining 55% is influenced by other variables outside this research model.